Analysis of electricity generation and clean coal technology development as greenhouse gas control strategy in Indonesia / Muhammad Heikal Hasan - Muhammad Heikal, Hasan (2013)
As Indonesian economic grow, electrical energy demand increased significantly over the last years. It is known that electrical industry is one of the largest sectors who contributed to the global CO2 emission besides transportation. Highly dependent in coal, fuel oil and diesel are the main causes of this problem. In the 20 years vision of Indonesian government, the country plans to construct coal fired power plant in the near future due to the abundance of coal reserves in the country and increase the share of renewable energy to meet the electricity demand as well as to cut the reliance in fuel oil. A clear view of 23 years trend of Indonesia’s electricity generation from 1987 to 2009 has been reviewed to show a pattern of electricity generation and emission of the country. In addition, Indonesian future power plant composition is investigated to predict fuel consumption and emission production of electricity generation until 2025. The result shows that most of CO2 emission is coming from steam turbine which uses coal as a fuel. Moreover, by increase the share of renewable energy do not gives any effect in CO2 emission reduction as the government intended to increase the supply of coal for electricity generation. However, there are some other policies and technology to control the emissions. In order to answer the energy demand, the government cannot avoid developing new coal-fired power plant to secure energy security of the country in the future. Besides encouraging energy efficiency, the only way to minimize negative impact of coal-fired power plant is by applying clean coal technology. To investigate the impact of clean coal technology on emission reduction, the simple mathematical model was selected as a method. The result showed clean coal technology could reduce CO2 emission up to 39% compare to conventional coal burning.In conclusion, by constructing more coal-fired power plant will give rise to the level of emissions that are dangerous to human health and will not resolve the energy sustainability problems. However, it may be able to sustain the energy security for a little longer until the development of new and renewable energy reach its best potential.